Administrative practices to promote Chinese language education and cultural exchange at Confucius Institutes around the world: a systematic review - Song, Meng; Sercu, Lies (Frontiers in Education, 2025)
As an intercultural educational program to promote Chinese language education and cultural exchange worldwide, the Confucius Institute (CI) has operated through specific managerial models since its establishment in 2004. This contribution reports the results of a systematic review conducted on the contents relevant to CIs’ administration in the post-2010 literature, aiming to map the status quo and the salient issues of CIs’ administration and provide take-away messages for administrators and researchers. Following PRISMA guidelines, 94 publications in English with research cases from 38 countries/regions were selected for thematic analysis conducted in NVivo. The analysis has revealed that CIs’ achievements of official administrative objectives are mainly situated in higher-order aspects (e.g., policies), whereas the practical sides (e.g., daily management) are prone to challenges. The lack of localization is also a recurring issue. To tackle the challenges, suggestions are provided for strengthening localization, improving educational leadership, and enhancing the cultivation of intercultural competence. The research outcomes emphasize significant theoretical advancements, including an improved theoretical framework for studying the administration of CIs and localization guidelines. These guidelines offer structured frameworks for administrators and researchers to systematically localize and conduct research on onsite operations at CIs.